Assessing Student Satisfaction With the Academic Environment at the University of Rajshahi: A Mixed Approach - Md. Mahbubul Alam; Md. Yeasir Arafat; Dr. Md. Sultan Mahmud (Penerbit Hellow Pustaka, 2025)
This study investigates the level of student satisfaction with the academic environment at the University of Rajshahi, aiming to contribute to a broader understanding of the quality of higher education in Bangladesh. The academic environment encompasses not only classroom experiences but also a range of institutional supports and services that facilitate student learning, development, and well-being. Adopting a mixed-method research design, the study integrates quantitative data from structured surveys with qualitative insights obtained through in-depth interviews and document analysis. This approach allows for a comprehensive understanding of the perceptions, expectations, and experiences of students across different faculties and academic years. The University of Rajshahi offers several academic and non-academic support mechanisms, including academic advising, counseling services, mentorship programs, library facilities, and financial aid, which collectively shape the students' academic journey. The research explores how effectively these services are delivered and whether they align with the diverse needs of the student population. Findings from the study are expected to reveal critical insights into institutional strengths and areas requiring improvement, with the aim of informing future policy initiatives and strategies to enhance academic satisfaction and overall educational quality at the university level in Bangladesh.